THE RELATIONSHIP AMONG THE MATHEMATICAL UNDERSTANDING, LEARNING MOTIVATION AND PARENT'S ATTENTION WITH STUDENTS MATHEMATICS LEARNING OUTCOMES - Meilinda Roestiyana Dewy; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Based on the observation in State Junior High School (SMP Negeri) 5, Kebumen obtained some information that the lack of student mathematics understanding, motivation learning is still low, and parents' lack of attention in learning activities. This study aims to determine the presence or absence of a positive relationship between and significant relationship among the mathematics understanding, motivation learning, and parent's attention with learning achievement mathematics students class VIII SMP Negeri 5 Kebumen academic year 2017/2018. This research population was the students of  VIII grade in SMP Negeri 5 Kebumen in 2017/2018, consisting of class  VIIIA, VIIIB, VIIIC, VIIID, VIIIE, and VIIIF, totaling 192 students. Samples were taken from VIIIB as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect the data motivation learning, parents' attention, and test method to understand math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between the intensity of learning, independent learning, and parents' attention with mathematics learning outcomes in students class VIII of SMP Negeri 9 Yogyakarta academic year of 2016/20167. It is showed by Fcount  Ftable is 6,333638138 > 3,340000 with  R = 0,635819872 and R2 = 0,4042669 with , with SR = , RC =  and RC = 44,76460 , EC = , EC =  and EC = .